EFFECT OF THE PROBIOTIC STREPTOCOCCUS SANGUINIS ON THE FORMATION OF STREPTOCOCCUS MUTANS BIOFILM IN ARTIFICIAL SALIVA - Rahmawati Sri Praptiningsih; Sheilia Siwi Pranantri; Anggun Feranisa (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Dental caries is a disease of the hard tissues of the teeth that most often occurs with a prevalence rate of about 45.3%. Dental caries is occuring because of the interaction between biofilms and carbohydrates from the food on the tooth surface (host). The caused by the biofilm formation is the presence of colonies of Streptococcus mutans bacteria. To reduce the accumulation of biofilms, mechanical and chemical methods can be used, namely using a toothbrush and mouthwash. Probiotics are widely used in dentistry because they have anti-plaque activity and form H2O2 which can reduce biofilm formation. Purpose: The purpose of this study was to determine the effect of the probiotic Streptococcus sanguinis on the formation of Streptococcus mutans biofilm in artificial saliva. Method: This research method was experimental analytic with post test only group design. The samples were 9 and divided into 3 groups, namely the probiotic group, Streptococcus sanguinis, the positive control group chlorhexidine and the negative placebo control group. Each group incubated in adhesion phase for 4 hours at 37°C. The formation of biofilms is measured by calculating the average results of Optical Density using an ELISA-reader. Data analysis was performed using the test One-way Anova. Results: The average values of optical density in the S. sanguinis, chlorhexidine and placebo groups, in sequence, were 0.374, 0.414, and 0.420. One-way Anova test obtained a significant value (p) of 0.014 (p<0.05) which indicates that there are significant differences in the probiotic group Streptococcus sanguinis, the chlorhexidine group, and the placebo group.  Conclusion: This study showed that the probiotic Streptococcus sanguinis had a significant impact on the formation of Streptococcus mutans biofilm in artificial saliva. Keywords :          Biofilm, Optical Density, Probiotic, Streptococcus mutans, Streptococcus sanguinis